2017
DOI: 10.1002/anie.201700494
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Catalytic Kinetic Resolution of Spiro‐epoxyoxindoles with Concomitant Asymmetric Friedel–Crafts Alkylation of Indoles

Abstract: An efficient process involving the catalytic kinetic resolution of racemic spiro-epoxyoxindoles with the simultaneous enantioselective Friedel-Crafts alkylation of indoles has been realized using a chiral phosphoric acid catalyst. The reaction provides two useful intermediates in high yields and excellent enantioselectivities. Performing the catalysis on a gram scale led to (R)-3-(3-indolyl)-oxindole-3-methanol, which was used in the asymmetric formal total synthesis of (+)-gliocladin C. Notably, the enantiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 69 publications
0
40
0
Order By: Relevance
“…After this initial success, we are again exploring alternative catalysts/solvents combination for the F‐C reaction of spiro‐epoxyoxindole. Eventually, we have observed that catalytic amount of Brønsted acid in organic solvent can also activate the spiro‐epoxide and lead to regioselective ring opening at the tertiary centre by the carbon nucleophiles likely indoles and arenes. Moreover, we have recently reported catalyst free on‐water ring opening reaction of spiro‐aziridineoxindole and indole .…”
Section: Introductionmentioning
confidence: 67%
“…After this initial success, we are again exploring alternative catalysts/solvents combination for the F‐C reaction of spiro‐epoxyoxindole. Eventually, we have observed that catalytic amount of Brønsted acid in organic solvent can also activate the spiro‐epoxide and lead to regioselective ring opening at the tertiary centre by the carbon nucleophiles likely indoles and arenes. Moreover, we have recently reported catalyst free on‐water ring opening reaction of spiro‐aziridineoxindole and indole .…”
Section: Introductionmentioning
confidence: 67%
“…Spiroepoxyoxindole is an easily accessible and strained compound that has been used in organocatalytic kinetic resolutions previously. 74,75 Thus, this compound represents an ideal substrate for testing our proposal. We chose spiroepoxyoxindole 1 and styrenyl boronic acid 10a as the coupling partners to screen reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, several challenges have to be considered: 1) the choice of an appropriate catalytic system to effectively control the regioselectivity, diastereoselectivity, and enantioselectivity, 2) the formation of a vicinal all‐carbon quaternary stereocenter, 3) the construction of a highly functionalized tetrasubstituted allene, and 4) overcoming the energy barriers associated with dearomatization. Considering the significant advantages of chiral phosphoric acids in the realm of asymmetric catalysis, we hypothesized that a double‐activation mode by hydrogen bonding could be applied to promote the asymmetric γ‐addition of 2,3‐disubstituted indoles to β,γ‐alkynyl‐α‐imino esters. If successful, this challenging process would provide an attractive approach for the efficient synthesis of fully substituted chiral α‐amino allenoates.…”
Section: Figurementioning
confidence: 99%